Proceedings of the 9th International Joint Conference on Biomedical Engineering Systems and Technologies 2016
DOI: 10.5220/0005825605070511
|View full text |Cite
|
Sign up to set email alerts
|

Inter-brain Synchronization between Nurse and Patient During Drawing Blood

Abstract: Tacit knowledge such as "proficient skills" and "knacks" in nursing skills seems not to be applied by nurse alone but by the interaction between nurse and patient. The purpose of this study is to analyze their interaction from the point of interbrain synchrony. In this study blood drawing technique was adopted as nursing skills and experiments of drawing blood were carried out in nurse-patient pairs. Experimental participants were 4 nurses and 6 patients. The brain waves in the occipital portion of nurse and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…This branch of research is concerned with understanding how neural synchrony, proposed between two or more brains, can occur and why. Recent InBS studies have found that weaker synchronisations occur when one member of a dyad reported having previously suffered anxiety (Kawano et al, 2016) or if members of the dyad were strangers compared to acquaintances (Atzil et al, 2012;Kinreich et al, 2017). 2-PNS argues that, particularly for social dynamics, the whole picture can be better represented by the findings from all interacting individuals (García and Ibáñez, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This branch of research is concerned with understanding how neural synchrony, proposed between two or more brains, can occur and why. Recent InBS studies have found that weaker synchronisations occur when one member of a dyad reported having previously suffered anxiety (Kawano et al, 2016) or if members of the dyad were strangers compared to acquaintances (Atzil et al, 2012;Kinreich et al, 2017). 2-PNS argues that, particularly for social dynamics, the whole picture can be better represented by the findings from all interacting individuals (García and Ibáñez, 2014).…”
Section: Introductionmentioning
confidence: 99%